PENCEGAHAN RINOSINUSITIS AKUT DENGAN MELAKUKAN CUCI HIDUNG MENGGUNAKAN LARUTAN SALIN ISOTONIS - Tiara Melati (Jurnal Akta Trimedika, 2024)
Nasal irrigation or douche with isotonic saline solution may be in rising due to COVID-19. But there has been a debate over its efficacy as a preventive measure for acute rhinosinusitis and other forms of acute upper respiratory infections. More randomized clinical trials and other literature have shown improvements in managing allergic rhinitis, chronic rhinosinusitis, and post-surgery patients. But few have demonstrated the significancy of saline nasal irrigation in otherwise. The European Position Paper on Rhinosinusitis and Nasal Polyps/EPOS 2020 has stated very few data was available to enable them to draw conclusion regarding nasal saline irrigation as adjunct treatment in acute rhinosinusitis. As we were in the endemic state of COVID 19, publication has risen to discuss the benefit of saline nasal douche. Literature search was conducted in PubMed and Elsevier databases. Inclusion criteria are recent publications (5 – 10 years), written in English, using Boolean method. Searching for keywords such as “nasal irrigation”, “nasal douche”, “nasal lavage”, “saline”, “acute rhinosinusitis”, and “common cold”. This review aims to discuss the latest data to answer whether isotonic saline nasal irrigation gives benefit as to prevent acute upper respiratory infections. All in all, this review recommends isotonic saline nasal douche safe to perform and may reduce prevalence and nasal symptoms in acute upper respiratory inflammation/ infection.